A survey of the value hierarchies of Anglo and Chicano students - Escotet, Miguel A. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A value hierarchy instrument was employed with two samples o f junior high school student belonging to the Anglo and the Chicano or Mexican American cultures. The sample consisted o f 155 students ranging in age from 12 to 14 years. An analysis of variance was used to the average rank assigned to each element in the instrument by Anglo and Chicano males and females. Also, Chi-square was computed for each value. Results from this instrument show slight differences in the value patterns o f Anglo and Chicano students. However, the value given to love by both cultures in regard to sex reveals significant differences intraculturally. The Chicano value pattern seems to be quite similar to the Anglo value pattern.